Thermoelectric Flexible Silver Selenide Films: Compositional and Length Optimization - Jie Gao; Lei Miao; Huajun Lai; Sijing Zhu; Ying Peng; Xiaoyang Wang; Kunihito Koumoto; Huanfu Cai (iScience, 2020)
Summary: Silver selenide is considered as a promising room temperature thermoelectric material due to its excellent performance and high abundance. However, the silver selenide-based flexible film is still behind in thermoelectric performance compared with its bulk counterpart. In this work, the composition of paper-supported silver selenide film was successfully modulated through changing reactant ratio and annealing treatment. In consequence, the power factor value of 2450.9 ± 364.4 μW/(mK2) at 303 K, which is close to that of state-of-the-art bulk Ag2Se has been achieved. Moreover, a thermoelectric device was fabricated after optimizing the length of annealed silver selenide film via numerical simulation. At temperature difference of 25 K, the maximum power density of this device reaches 5.80 W/m2, which is superior to that of previous film thermoelectric devices. Theoretically and experimentally, this work provides an effective way to achieve silver-selenide-based flexible thermoelectric film and device with high performance. : Electrochemical Materials Science; Materials Synthesis; Energy Materials Subject Areas: Electrochemical Materials Science, Materials Synthesis, Energy Materials